Well-Being and Wellness in the Twenty-First Century: A Theanthropocosmic Approach - Modise, Leepo (Journal of religion and health, 2016)
In this paper, clarification and definition of the concept well-being of human beings are reflected upon from a faith perspective. The author will define well-being and wellness within the following conceptual definitions: firstly, well-being and wellness will be defined in term of African-Christian approach (the interconnectedness of God-human-and-world approach). Secondly, the author will focus on differentiation of well-being and wellness in a human being. Thirdly, the focal point will be on the mixing of holistic, dualist and triadic approaches to define well-being.